Mimicry and Prosocial Behavior - van Baaren, Rick B.; Holland, Rob W.; Kawakami, Kerry; van Knippenberg, Ad (Psychological Science, 2004)
Recent studies have shown that mimicry occurs unintentionally and even among strangers. In the present studies, we investigated the consequences of this automatic phenomenon in order to learn more about the adaptive function it serves. In three studies, we consistently found that mimicry increases pro-social behavior. Participants who had been mimicked were more helpful and generous toward other people than were non-mimicked participants. These beneficial consequences of mimicry were not restricted to behavior directed toward the mimicker, but included behavior directed toward people not directly involved in the mimicry situation. These results suggest that the effects of mimicry are not simply due to increased liking for the mimicker, but are due to increased prosocial orientation in general.